Geomagnetically induced current characteristics in southern Africa - Ngwira, Chigomezyo Mudala (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2009)
Geomagnetically induced currents (GICs), resulting from adverse space weather, have been demonstrated to cause damage to power transformers at mid-latitudes. There is growing concern over possible GIC effects in the Southern African network due to its long power lines. Previous efforts to model the electric field associated with GICs in the Southern Africa region used a uniform ground conductivity model. In an effort to improve the modelling of GICs, GIC data together with Hermanus Magnetic Observatory geomagnetic field data were used to obtain a multilayered ground conductivity model. This process requires a definition of the network coefficients, which are then used in subsequent calculations. This study shows that GIC computed with the new network coefficients and the multilayered ground conductivity model improves the accuracy of GIC modelling. Then GIC statistics are derived based on the recordings of the geomagnetic field at Hermanus, the new network coefficients and ground conductivity model. The geoelectric field is modelled using the plane wave method. The properties of the geomagnetic field, their time derivatives and local geomagnetic indices were investigated to determine their characteristics in relation to the GIC. The pattern of the time derivatives of the horizontal geomagnetic field closely follow the rate of change of the north-south geomagnetic component rather than the east-west component. The correlation between the GIC and the local geomagnetic field indices was also investigated. The results show that there is a higher correlation between the GIC and the east-west components of the geomagnetic local indices than between the GIC and the north-south components. This corresponds very well with the orientation of the power lines feeding the power transformers at the South African Grassridge electrical substation GIC site. Thus, the geoelectric field driving the GIC at Grassridge is north-south oriented. Further, it is shown that the geomagnetic observation sites have a strong directional preference with respect to the Grassridge GIC site.
Keywords: Magnetic Observatory (South African Council for Scientific and Industrial Research) Geomagnetism -- Africa; Southern Computer networks -- Africa, Southern Magnetospheric currents